Technology Acceptance Factors Affecting Consumer’s Buying Decision Process of Furniture and Home Decoration via Online - Phopueannoi, Chanattha; Kosakarika, Sirirat (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The purposes of this research were: 1) to consumer’s buying decision process of furniture and home decoration via online channels in Bangkok with different demographic characteristics and 2) to investigate technology acceptance factors affecting consumer’s buying decision process of furniture and home decoration via online channels in Bangkok. The sample size concluded 400 customers, who bought furniture and home decoration via online channels and also lived in Bangkok. A research tool was the questionnaires with a confidence index of 0.95. The statistics used in the research were frequency, percentage, mean, standard deviation, t-test, F-test and multiple regression analysis at a statistical significance level of .05. The research result revealed that most of the samples are female; age between 21-30 years old; Bachelor’s degree; employee and having income between 25,001-35,000 THB per month. The overall level technology acceptance factors were at the agree level of opinion. The overall buying decision process were at a high level. Results of the hypotheses indicated that the consumers with different average monthly incomes affect the buying decision of furniture and home decoration via online channels differently all process and consumers of different ages influence the buying decision process in the information search, evaluation of alternative and post - buying behavior. Furthermore, perceived ease of use significantly affected on buying decision of furniture and home decoration via online channels all process and perceived usefulness significantly affected on buying decision process in the problem recognition, information search, evaluation of alternative and decision making.